First reports of the sexual morphs of Diaporthe forlicesenica nom. nov. and Diaporthe goulteri (Diaporthaceae, Diaporthales) revealed by molecular phylogenetics - Bundhun, Digvijayini; Senanayake, Indunil C.; Jayawardena, Ruvishika S.; Camporesi, Erio; Huang, Yinghua; Dong, Zhangyong; Hyde, Kevin D.; To-Anun, Chaiwat; Cheewangkoon, Ratchadawan (Phytotaxa, 2021)
Diaporthe forlicesenica nom. nov. is proposed for D. dorycnii Dissan., Camporesi & K.D. Hyde, a later homonym of D. dorycnii (Mont.) Sacc. Diaporthe forlicesenica as well as the species D. goulteri have so far only been described in their asexual morphs. In this study, the sexual morphs for these species are recovered for the first time, from the dead branches of Cytisus sp. in Italy and from an unknown host in Thailand. The asexual-sexual morph connections of the species are confirmed by DNA sequence based phylogenetic analyses including the ITS, tef1, tub2 and his loci, supported by morphology. Detailed descriptions, illustrations and molecular data for the taxa are provided.